2003
DOI: 10.1046/j.1523-1755.2003.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Maps of end-stage renal disease and amounts of angiotensin-converting enzyme inhibitors prescribed in Japan

Abstract: The renal protective effects of ACE inhibitors have been established by results with animal models of progressive nephropathy and large-scale clinical trials. Our epidemiologic results for Japan as a whole show the same protective effects still more convincingly from a different approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 18 publications
1
42
1
Order By: Relevance
“…(6), delay the progression from incipient nephropathy to overt nephropathy (7) and from overt nephropathy to endstage renal disease (ESRD) (8,9 (10)(11)(12), and this regional difference was inversely correlated with the amount of RAS inhibitors prescribed ( Fig. 1) (13,14). These findings have been demonstrated in a nationwide scale that in fact RAS inhibitors were working to suppress ESRD in clinical practice.…”
Section: Repeated Renal Biopsy In Diabetic Nephropathy After Pancreasmentioning
confidence: 55%
“…(6), delay the progression from incipient nephropathy to overt nephropathy (7) and from overt nephropathy to endstage renal disease (ESRD) (8,9 (10)(11)(12), and this regional difference was inversely correlated with the amount of RAS inhibitors prescribed ( Fig. 1) (13,14). These findings have been demonstrated in a nationwide scale that in fact RAS inhibitors were working to suppress ESRD in clinical practice.…”
Section: Repeated Renal Biopsy In Diabetic Nephropathy After Pancreasmentioning
confidence: 55%
“…Usami et al [15] reported that the intake of angiotensinconverting enzyme inhibitors in Okinawa was lower than that in other parts of Japan, suggesting the insufficiency of CKD therapy in Okinawa. Because the income levels in Okinawa are the lowest in Japan, cheaper drugs are preferred.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, although 50.2% of males and 38.3% of females aged 40 years or older in Ibaraki Prefecture showed hypertension, only 41.9% and 49.2% of them, respectively, were receiving antihypertensive treatment [13], and blood pressure was not adequately controlled in about 50% of those who were receiving treatment [14]. Appropriate interventions are assumed to bring about noticeable effects in Japan, in which RAS inhibitors have not been used effectively as antihypertensive therapy, although a slight increase has occurred in recent years [15].…”
Section: Introductionmentioning
confidence: 92%